Embracing sustainability: the incorporation of sustainability principles in municipal planning and policy in four mid-sized municipalities in Ontario, Canada. Issue 2 (1st February 2016) - Stuart, John; Collins, Patricia; Alger, Morgan; Whitelaw, Graham
Abstract : The issue of planning for sustainability is becoming more established within Canadian municipal planning. As municipalities begin to align their planning policy to reflect a more sustainable approach, there is an increased interest in how sustainability is being operationalised within municipal documents. This research aims to better understand how principles of sustainability are imbedded within Ontario municipal documents, with a specific focus on the Integrated Sustainability Community Planning approach that has emerged in Canada. Drawing on a nested comparative case study of four mid-sized municipalities, we uncover the language and strategies employed by the municipalities as they relate to the principles of sustainability developed by Gibson [2006a. Sustainability assessment: basic components of a practical approach. Impact Assessment and Project Appraisal, 24 (3), 170–182]. The findings suggest that current policy-based approaches to sustainability are considering more socially oriented strategies focused on promoting community involvement, inclusive decision-making, equity, socio-ecological civility, long-term integrative planning, and responsibility through stewardship. However, there are potential limitations that will require future research to examine policy outcomes associated with sustainability uptake. The ICSP approach must still overcome the issues relating to lack of regulatory authority and the incorporation of policies based on popular trends rather than empirical evidence.